A population‐based study of the comparative effectiveness of second‐generation antipsychotics vs older antimanic agents in bipolar disorder. (21st September 2016) - Bauer, Mark S; Miller, Christopher J; Li, Mingfei; Bajor, Laura A; Lee, Austin
Abstract : Objectives: Numerous antimanic treatments have been introduced over the past two decades, particularly second‐generation antipsychotics (SGAs). However, it is not clear whether such newer agents provide any advantage over older treatments. Methods: A historical cohort design investigated the nationwide population of outpatients with bipolar disorder treated in the Department of Veterans Affairs who were newly initiated on an antimanic agent between 2003 and 2010 (N=27 727). The primary outcome was likelihood of all‐cause hospitalization during the year after initiation, controlling for numerous demographic, clinical, and treatment characteristics. Potential correlates of effect were explored by investigating time to initiation of a second antimanic agent or antidepressant. Results: After control for covariates, those initiated on lithium or valproate monotherapy, compared to those beginning SGA monotherapy, were significantly less likely to be hospitalized, had a longer time to hospitalization, and had fewer hospitalizations in the subsequent year. Those on combination treatment had a significantly higher likelihood of hospitalization, although they also had a longer time to addition of an additional antimanic agent or antidepressant. Conclusions: The present analysis of a large and unselected nationwide population provides important complementary data to that from controlled trials. Although various mechanisms may be responsible for the results, the data support the utilization of lithium or valproate, rather than SGAs, as the initial antimanic treatment in bipolar disorder. A large‐scale, prospective, randomized, pragmatic clinical trial comparing the initiation of SGA monotherapy to that of lithium or valproate monotherapy is a logical next step.